The Herodotus’ logoi on Ancient ethne: A New Collection of Papers on Ethnicity and Identity in Antiquity - Sinitsyn, Aleksandr A.; Surikov, Igor E. (Anabasis. Studia Classica et Orientalia, 2020)
The authors of the article briefly review the content of certain parts and analyze the whole collection devoted to ethnology-cultural issues of Antiquity as seen through the prism of Herodotus’ Histories: Thomas Figueira / Carmen Soares (eds.), Ethnicity and Identity in Herodotus, London / New York: Routledge 2020, XI, 341 p., ISBN: 978-1-138-63111-3.